Prevalence of lactase deficiency in British adults. Issue 2 (February 1984) - Ferguson, A; MacDonald, D M; Brydon, W G
Abstract : The prevalence of lactase deficiency in British adults is unknown. Examination of the distribution of lactase activities in single and multiple biopsies of jejunum indicated that 0.8 U/g wet weight was a suitable cut-off point to separate lactase deficient patients from others. One hundred and fifty white British adults were selected, none of whom had significant intestinal disease and all of whom had normal histopathology of a jejunal biopsy and normal activities of other disaccharidases measured in the biopsy. The prevalence of lactase deficiency in this group was 4.7%. In contrast, 15 of 20 non-white adults were lactase deficient. Lactase deficiency was found in only three of 36 patients investigated because of diarrhoea after gastric surgery, and in 16 of 200 patients with irritable bowel syndrome (8%). As the prevalence of lactase deficiency is no higher in irritable bowel syndrome than in 'normal' individuals, lactase deficiency clearly is not a predisposing factor for irritable bowel syndrome in white British adults although the two conditions may occasionally coexist.